2022
DOI: 10.1186/s40510-022-00420-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and comparing the duration of adolescent growth peak in skeletal class I and III subjects using cervical vertebral maturation method

Abstract: Background Estimating skeletal maturation and growth potential is essential for developing adolescents' best orthodontic treatment plan. The purpose of this study was to compare the duration of adolescent growth peak in subjects of skeletal classes I and III using the cervical vertebral maturation (CVM) method. Methods This retrospective cross-sectional study included 116 Iranian subjects (skeletal class I = 68, skeletal class III = 48) aged 8–16 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The recovery growth may explain another part of this recurrence when maxillary protraction use was discontinued before facial growth was complete [ 15 , 17 ]. Untreated Class III subjects tend to have a longer mandibular growth spurt than class I adolescents, which lasts until young adulthood, especially in males [ 5 , 19 ]. This raised the possibility of relapse if there is a rebound of the mandible growth after the end of maxillary protraction.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery growth may explain another part of this recurrence when maxillary protraction use was discontinued before facial growth was complete [ 15 , 17 ]. Untreated Class III subjects tend to have a longer mandibular growth spurt than class I adolescents, which lasts until young adulthood, especially in males [ 5 , 19 ]. This raised the possibility of relapse if there is a rebound of the mandible growth after the end of maxillary protraction.…”
Section: Discussionmentioning
confidence: 99%
“…Children's respiratory disease as a contributing factor may indicate this significant difference (14) . On the other hand, Naderi et al; 2022 concluded that CVM stages 2, 3, and 4 failed to achieve an adequate diagnostic reliability in identifying the mandibular development peak (15) .…”
Section: Discussionmentioning
confidence: 99%